Nickel Exposure Has Complex Transgenerational Effects in a Butterfly. (16th July 2018) - Kobiela, Megan E; Snell-Rood, Emilie C
Abstract: Heavy metal pollution is a major problem in urban and industrial environments, and has a myriad of negative effects on animals. Quantifying the amount of population-level variation that exists for heavy metal tolerance and how plastic responses to heavy metals play out across generations are essential for understanding how animals respond to pollution. As an initial step toward studying transgenerational effects and population-level variation in concert, we brought cabbage white butterflies ( Pieris rapae ) from two populations—collected from St. Paul, MN, and Davis, CA—into common conditions and fed them a diet dosed with nickel. To measure transgenerational effects, we reared a second generation in a fully factorial design, within each population, to achieve all combinations of parent and offspring exposure to nickel or control diets. Across both generations, we quantified survival and other fitness-related traits, including development time, body size, and egg size and number. We found both population differences and complex transgenerational effects, including a positive effect of nickel on survival and development time in one of the populations. Overall, nickel exposure was stressful in one population, mainly after two generations of exposure, and had neutral or slightly positive effects on the other. We found no evidence for costs of mismatch between parental and offspring environments. While the reasons for the differences observed between the two populations are unclear, the variation in nickel tolerance observed in this species suggests that some organisms may be less affected by low levels of heavy metal pollution in urban and industrial areas than expected.